2023
DOI: 10.3390/met13061083
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Corrosion Behavior of Ti-N-O Modified Layer on the TC4 Titanium Alloy Prepared by Hollow Cathodic Plasma Source Oxynitriding

Abstract: TC4 alloy is widely used in dental implantation due to its excellent biocompatibility and low density. However, it is necessary to further improve the corrosion resistance and surface hardness of the titanium alloy to prevent surface damage that could result in the release of metal ions into the oral cavity, potentially affecting oral health. In this study, Ti-N-O layers were fabricated on the surface of TC4 alloy using a two-step hollow cathode plasma source oxynitriding technique. This resulted in the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The chemical surface heat treatment methods mainly include nitriding, carburizing, oxidating, and boronizing. Nitriding treatment is the most commonly used chemical heat treatment method for titanium metal surfaces, including gas nitriding, plasma nitriding, and laser nitriding [ 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 ]. The nitriding temperature of titanium metal is much higher than that of steel materials.…”
Section: Surface Modification Methodsmentioning
confidence: 99%
“…The chemical surface heat treatment methods mainly include nitriding, carburizing, oxidating, and boronizing. Nitriding treatment is the most commonly used chemical heat treatment method for titanium metal surfaces, including gas nitriding, plasma nitriding, and laser nitriding [ 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 ]. The nitriding temperature of titanium metal is much higher than that of steel materials.…”
Section: Surface Modification Methodsmentioning
confidence: 99%
“…Authors have reported that in the cathodic layer occurs a hydrogen evolution; that behavior can sensitize the anodized and provoke a faster anodization dissolution, as is shown for the anodization of Ti-6Al-4V in NaOH. The Ti-6Al-4V anodized in KOH showed regeneration of the passive layer, but a dissolution process occurred, so the passive layer generated is not protective enough [54].…”
Section: Cyclic Potentiodynamic Polarizationmentioning
confidence: 97%